Developing Language Study Textbooks: An Effort to Understand Discourse Theory Using Basic Literacy Based on Problem Solving Model - Purwati, Panca Dewi; Afifah, Nur Ummi (Universitas Pendidikan Mandalika, 2025)
Discourse material and discourse theory are two different studies, but both are important to be mastered by students of the Elementary School Teacher Education Study Program (PGSD) as provisions for becoming professional teachers. The results of the assessment through the ujian.ac.id application show that the average score of students' understanding of discourse theory has not yet reached completion. Based on the needs analysis, it is necessary to develop an Indonesian Language Study textbook as a contextual learning resource that also functions as basic literacy material through habituation, development, and learning activities. This study aims to: describe the results of the textbook validation test, and describe the results of the textbook effectiveness test. The study used the Research and Development (R&D) method of the Borg & Gall model which was simplified into seven stages. The validation results by material experts obtained an average score of 4.27 with the category